A study on the determinants of employees’ job satisfaction at National Heart Institute (IJN) / Norfarhanah Zulkefli and Noor Azanah Najwa Raimee - Zulkefli, Norfarhanah; Raimee, Noor Azanah Najwa (Faculty of Business and Management, 2016)
Employees’ job satisfaction becomes a common issue faced by many employers today. The purpose of this study was to identify the level of employees’ job satisfaction, to determine the relationship, and the dominant factors. It is important for an organization to recognize the level of employees’ job satisfaction, the relationship and dominant factors to gain commitment from their workers as well as to able them to achieve the organization objective. The independent variable of this study refers to working environment, career development, training and rewards. 100 respondents were chosen from the total population from six departments in the organization by using simple random sampling. To accomplishing the research objectives, the researchers used questionnaire as the method to collect all the data from the respondents. From the findings of the study, working environment, career development, and reward have significant relationship with employees’ job satisfaction, while training is not the significant predictor for employees’ job satisfaction. The researchers also found that career development is the most significant predictor variable. In overall, all the objectives of this research are able to answer by the researchers.